Design And Development Of A Single Vane Rotating Sleeve Rotary Compressor For Refrigeration System - Mohd Yusof, Taib (2010)

(untitled)
Preliminary test of a single vane rotating sleeve rotary compressor for refrigeration system application is presented in this paper. Generally, single vane rotating sleeve rotary compressor is a type of rotary compressor family that has been developed recent years. The characteristics of the compressor design and compression concept in such that of this compressor is supposed to be better than others rotary compressor in term of leakage and friction. The operation of the compressor mechanism is directly from the shaft to the mechanism compression components. This mean that when the shaft start to rotate, the mechanism compression components will be rotate together in the same direction and this mechanism is able to compress the refrigerant at all speed of rotation. This is because the design of the vane tip is embedded in the swing slot at the rotating sleeve and the other end side of vane is embedded into the rotor slot. The fabrication of prototype of the compressor needs the concentration because it is involving the high precision of machining and mostly of the tolerance was applied in this design is around 5 m to 20 m. Computational analysis of the design shows that the design specification is safe to be applied in refrigeration system with the maximum stress distribution of 31 MPa and deflection 0.55 μm.